2023
DOI: 10.1002/bse.3446
|View full text |Cite
|
Sign up to set email alerts
|

Forging organizational resilience through green value co‐creation: The role of green technology, green operations, and green transaction capabilities

Abstract: The study assessed the mediating role of green organizational capabilities (green technology development, green operations, and green transactions), in the relationship between green value co‐creation and organizational resilience among Chinese manufacturing firms, that is, firms' ability to build strong organizational resilience in response to the COVID‐19 pandemic. It focused on manufacturing firms operating within Shenzhen, a coastal city located within the Guangdong province in southeastern China. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Harman’s one-factor test was run, as a statistical measure of CMB (Borah et al , 2023). Results demonstrated that, when the extracted factor was fixed at 1, the single extracted factor had a variance of 31.44% (less than 50%).…”
Section: Methodsmentioning
confidence: 99%
“…Harman’s one-factor test was run, as a statistical measure of CMB (Borah et al , 2023). Results demonstrated that, when the extracted factor was fixed at 1, the single extracted factor had a variance of 31.44% (less than 50%).…”
Section: Methodsmentioning
confidence: 99%
“…Manufacturing firms are much concerned about GVCC, and the GC filled this gap by showing a significant relationship between each other (Borah, Dogbe, Dzandu, & Pomegbe, 2023). Firms are suggested to devote time and energy to promoting GVCC (Chang, 2019), which emphasize the significant impact of market and consumer interactions in forming production, services, and design (Mafuwane et al, 2023).…”
Section: The Mediating Role Of Gvccmentioning
confidence: 99%
“…Based on this logic, green initiatives prove to be a relevant path to a certain independence and mitigation of dependence on external resources. These can be seen as additional capabilities that build the independence and resilience of the organization, even during Covid‐19 as Borah et al (2023) noted. In contrast, it can also be a way to improve firm reputation and image leading to good relationships with powerful stakeholders, thereby enabling firms to access crucial resources that are rare and hard to obtain.…”
Section: Underlining Theories and Their Nexusmentioning
confidence: 99%